Sublobar resection with intraoperative brachytherapy versus sublobar resection alone for early-stage non-small-cell lung cancer: a meta-analysis. (25th May 2021) - Chen, Enli; Wang, Juan; Jia, Chenfei; Min, Xueya; Zhang, Hongtao
Abstract:  : OBJECTIVES: The purpose of this study was to compare the clinical outcomes for sublobar resection (SR) or SR plus intraoperative brachytherapy (SRB) for clinical stage I non-small-cell lung cancer. METHODS: A systematic search was performed in the EMBASE, PubMed and Cochrane Library databases to identify related studies comparing SR to SRB. Data were collected on local recurrence (LR) as a primary outcome and regional or distant recurrence, overall survival and disease-free survival (DFS) as secondary outcomes. Meta-analysis was carried out using Stata 12.0. RESULTS: A total of 476 patients received SRB, and 617 received SR across 5 studies. Meta-analysis of LR, regional or distant recurrence, overall survival and disease-free survival rates showed no significant difference between SRB and SR groups. However, when biologically effective dose (BED) was >100 Gy, LR rate was lower in the SRB group than in the SR group (Relative risk [RR] = 0.143, 95% confidence interval [CI]: 0.051-0.397) (p < 0.001). When BED was <100 Gy, no significant difference was found in LR rate between SRB and SR groups (SRB versus SR: RR = 1.132, 95%CI: 0.704-1.821) (p = 0.608). CONCLUSIONS: Intraoperative brachytherapy was not associated with reduced risk of regional or distant metastasis or improved outcomes for patients with clinical stage I non-small-cell lung cancer; however, it might reduce the LR rate when BED was >100 Gy.